Cyrus Console's The Odicy and epic ecology. (30th May 2018) - Eccleston, Sasha-Mae
Abstract: This article considers the relationship between Cyrus Console's 2011 experimental poetry collection, The Odicy (2011), and Homer's Odyssey . It argues two points: (1) The Odicy 's ecopoetics reframe the stakes of Odyssean recognition for an age on the brink of ecological crisis; (2) by topicalizing the limits of contemporary signification it reworks The Odyssey 's self-reflexive ecological and metapoetic thinking. Its goal as an adaptation is not to tell the Odyssean narrative, but to enact a consideration of Odyssean questions regarding language, signification, and recognition given current political economies of language in the USA. Its experimentation and acknowledgement of experimentation's limits render The Odicy a σῆμα for our times.